Recent advances in radiation oncology: multimodal targeting of high risk and recurrent prostate cancer. Issue 3 (May 2018) - Kwok, Young; Kaiser, Adeel; Rice, Stephanie R.; Cohen, Randi; Mishra, Mark
Abstract : Purpose of review: The overview summarizes recent developments in radiation oncology for high risk and recurrent prostate cancer. Recent findings: A number of well known phase III prostate hypofractionated radiation therapy (HFxRT) trials were finally published with long-term follow-ups. These trials demonstrate patterns of equivalent tumor control with several showing worse toxicity rates. The ASCENDE-RT randomized trial demonstrated the superiority of brachytherapy boost in intermediate and high-risk prostate cancer. Important randomized trials show a clear benefit to androgen deprivation therapy (ADT) in both intermediate-risk prostate cancer and postprostatectomy patients with rising PSA. Finally, the first randomized trial of metastasis-directed therapy showed a delay in time to ADT and biochemical failures in oligometastatic prostate cancer. Summary: The use of brachytherapy boost in high-risk disease and ADT in locally recurrent cancer after prostatectomy are practice changing given the magnitude of benefit seen in the randomized trials. The benefit of metastasis-directed therapy in oligometastatic prostate cancer must be validated in a larger randomized trial. However, hypofractionated radiation therapy requires further long-term follow-up so that late toxicity risk can be accurately assessed before it becomes a standard of care in prostate cancer.